2020
DOI: 10.1111/jac.12450
|View full text |Cite
|
Sign up to set email alerts
|

Bean–soybean succession under full sun and in agroforestry systems: Impacts on radiation use efficiency, growth and yield

Abstract: Simultaneous cultivation of agricultural and forest species may result in changes in plant community interactions, generating microclimatic changes within the understory and then modifying growth and yield characteristics of the intercropping systems. Thus, this study aimed to assess the radiation use efficiency, growth and yield of bean and soybean cultivated in succession under two arrangements of agroforestry and full sun. To these ends, two field experiments were conducted in Southern Brazil: bean in‐seaso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Integrated Crop-Livestock-Forestry systems cannot be expected to fully replace monoculture farming. In particular, soybean plants grown under integrated systems had lower yields because of reduced solar incidence 12 . However, land-use diversification does not need to follow a single prescription for all cases.…”
Section: Solutions Through Diversificationmentioning
confidence: 99%
“…Integrated Crop-Livestock-Forestry systems cannot be expected to fully replace monoculture farming. In particular, soybean plants grown under integrated systems had lower yields because of reduced solar incidence 12 . However, land-use diversification does not need to follow a single prescription for all cases.…”
Section: Solutions Through Diversificationmentioning
confidence: 99%
“…Several strategies can be used to reduce the effect of the tree canopy on solar radiation, such as forest species by adjusting the canopy size, architecture and leaf geometry [40]. Several studies showed that the dynamics of solar radiation in understorey forest species differed, 41.5% in the amount of solar radiation available in understorey Melaleuca cajuputi, Peltophorum dubium and Eucalyptus grandis [41].…”
Section: Soybean In Agroforestry Systemmentioning
confidence: 99%